Evaluation of natural zeolite for volatile organic compound (acetic acid) and humidity control in ambient hygrothermal conditions of Philippine archives - Albano, Nikko B.; Gili, Mon Bryan Z.; Rey, Emma M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2024)
It is known in conservation science that paper degradation is caused by humidity, and volatile organic compounds (VOCs). Studies have also shown that both desiccants and pollutant scavengers are useful in archives in preventing paper degradation. Activated carbon, silica gel and zeolite are absorbents that can act as desiccants and pollutant scavengers. Acetic acid, common in paper repositories, was chosen as a model VOC, following previous similar studies. This study compares natural zeolite against activated carbon and silica gel as established desiccants and pollutant scavengers in archival boxes by evaluating their effectiveness in reducing humidity in archival boxes and acidity in paper while exposed to acetic acid. This study found natural zeolite as a good or event better than silica gel while activated carbon was found to be ineffective for VOC control but found all three to be ineffective for humidity control in ambient conditions. This study also found some microwave oven drying to be effective for regenerating natural zeolite.
Thesis
Keywords: Zeolites; Volatile organic compounds; Archives -- Environmental aspects -- Philippines